Double germline mutations in APC and BRCA2 in an individual with a pancreatic tumor - Göhringer, Caroline; Sutter, Christian; Kloor, Matthias; Gebert, Johannes; Keller, Monika; Treiber, Irmgard; Ganschow, Petra; Kadmon, Martina; Moog, Ute (Familial cancer, 2017)
We report on three brothers affected by pancreatic tumors, all due to different causes, including mutations associated with two different cancer predisposition syndromes in the same individual. In the index patient a germline mutation both in the APC and BRCA2 gene was identified while one affected brother showed the BRCA2 mutation only and another brother is supposed to have developed pancreatic cancer due to multiple non-genetic risk factors. We outline the impact of a double germline mutation in two tumor predisposition genes in one individual and proven heterogeneity of multiple cases of pancreatic tumors in one family. With the growing implementation of next generation sequence based panel testing for multiple genes involved in tumor predisposition syndromes, relevant variants in two (or more) genes will be found more frequently. This family illustrates the importance of family studies, especially when using gene panel tests.